Genetic Diversity and Relatedness Within and Among Northern Bobwhite Coveys in South Texas - Katherine S. Miller; Leonard A. Brennan; Randy W. DeYoung; Fidel Hernández; X. Ben Wu (National Quail Symposium Proceedings, 2017)
Although biologists have studied northern bobwhite (Colinus virginianus) genetic diversity and population structure, there is little known about the genetic diversity, structure, and relatedness of their winter coveys. Both flexible mating strategies and the fall shuffle may have implications for inbreeding and genetic diversity in northern bobwhite populations. Our goal was to determine genetic diversity and relatedness for coveys on a private ranch in Jim Hogg County in South Texas. During the 2010–2011 and 2011–2012 hunting seasons, 96 northern bobwhites were sampled from 29 coveys. We analyzed 11 northern bobwhite microsatellite DNA loci, measured genetic structure with an Analysis of Molecular Variance and FST, and determined an inbreeding coefficient (Fi). We determined Queller and Goodnight’s coefficients of relatedness (R) and then used a maximum-likelihood algorithm in COLONY to assign relationships (parent–offspring, full siblings, and half siblings). Most genetic variation (92%) was within coveys. The overall FST was 0.073, indicating moderate genetic structure among coveys. Relationship coefficients ranged from –0.82 to 1.00 but most of the bird pairs were unrelated (R = -0.004 ± 0.002 SE). In 2010–2011, COLONY assigned 130–149 half sibling, 1–4 full sibling, and 0–3 parent-offspring pairs (n = 2,887, 5 trials, probability >0.99). Thirteen coveys (56%) had related individuals (n = 20 pairs). In 2011– 2012, COLONY assigned 5–10 half sibling and 1 full sibling pairs (n = 161). Two coveys (33%) had related individuals (2 pairs). The occurrence of relatives in different coveys suggests that the fall shuffle is effective at mixing families and the high half sibling count among coveys may suggest polygamy. These strategies may help northern bobwhite populations maintain moderate genetic diversity.
Keywords: colinus virginianus; northern bobwhite; covey dynamics; full sibling; half sibling; relatedness; south Texas